The role of overweight, obesity and exercise therapy on low-back pain - Karol Zagórski; Mateusz Kozik; Nina Skalska-Dziobek; Weronika Małagocka; Karolina Chybowska; Maria Naruszewicz; Aleksandra Midro; Przemysław Cetnarowski (Quality in Sport)
Introduction and purpose: Low back pain (LBP) is a leading cause of impairment worldwide and its occurrence is still growing. There are many modifiable risk factors contributing to developing LBP, especially obesity, smoking and physical work. In spite of a breakthrough in pharmacotherapy, lifestyle changes and exercise remain the primary prophylactic and treatment options. The aim of this paper was to summarize the data available in the literature and recent reports about the effect of obesity and overweight on LBP and the effectiveness of different exercise programs.